Pemilihan Para Murid sebagai Karya Kesatuan Bapa dan Anak: Sebuah Kajian Eksegetis mengenai Relasi dan Karya Bapa dan Anak dalam Yohanes 6: 60-71 - Finki Rianto Kantohe (STFT Jakarta, Indonesia, 2022)
When exploring the unity of the Father and the Son in the Gospel of John, scholars tend to skip John 6:60-71. This section portrays the unity of the Father and the Son that has significant theological implications for the church’s soteriology and ecclesiology. The author argues that John 6:60-71 depicts the unity of the Father and the Son in selecting the disciples. This view implies that salvation and the fellowship of believers are the work of the Father and the Son. The author reviews several aspects: the gospel’s historical and literary contexts, including the structure of the gospel, the exegesis of John 6:60-71 and its theological implications on the aspects of the unity of the Father and the Son. Finally, this paper concludes with the idea that salvation and the fellowship of believers are the work of the Father and the Son described in John 6: 60-71.